2006
DOI: 10.1086/505416
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Energy Release during the 2002 September 9 Solar Flare

Abstract: We study the magnetic energy release during the 2002 September 9 flare using the high-cadence (40 ms) H filtergram at Big Bear Solar Observatory (BBSO), along with hard X-ray and microwave data from the Reuven Ramaty High-Energy Solar Spectroscopic Imager (RHESSI ) and the Owens Valley Solar Array (OVSA), respectively. We take the Poynting vector approach with the standard two-dimensional geometry of the reconnecting current sheet (RCS) but suggest a new technique to infer the area of the RCS, in order to comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 29 publications
2
27
0
Order By: Relevance
“…u ∼ e namely, HXR sources should move fast during the flare maximum phase and slowly at other times. An episodic variation of ribbon motion with the HXR light curves found by Lee et al (2006) does support this idea. However, there are also counterexamples: Krucker et al (2003) found a correlation of HXR light curves with parallel, rather than perpendicular, motions of HXR sources with respect to the PIL.…”
Section: Introductionmentioning
confidence: 75%
“…u ∼ e namely, HXR sources should move fast during the flare maximum phase and slowly at other times. An episodic variation of ribbon motion with the HXR light curves found by Lee et al (2006) does support this idea. However, there are also counterexamples: Krucker et al (2003) found a correlation of HXR light curves with parallel, rather than perpendicular, motions of HXR sources with respect to the PIL.…”
Section: Introductionmentioning
confidence: 75%
“…Forbes & Priest (1982) proposed a method for estimating the reconnection rate based on the separation rate of the Hα footpoints. Implementation of the method yields speeds from tens to as high as 200 km s −1 ( Jing et al 2005;Lee, Gary & Choe 2006). A sense of how dynamical these processes are can be obtained from movies such as those made from TRACE data, available at http://trace.lmsal.com/POD/TRACEpod.html.…”
Section: Reconnection Observedmentioning
confidence: 99%
“…The first is through measurements made by directly observing inflows at the coronal reconnection site, and estimating the inflow Mach number (M ≡ V in /V A ) with a certain assumption or estimate of coronal magnetic field and plasma density at the reconnection site (Yokoyama et al, 2001;Lin et al, 2005). The second approach derives reconnection rate in terms of reconnecting electric field (in a 2D approximation, but see Lee and Gary, 2008, concerning modifications to 3D) or reconnection flux (in a general configuration) by observing flare evolution in the lower atmosphere (Poletto and Kopp, 1986;Fletcher and Hudson, 2001;Isobe et al, 2002;Isobe, Takasaki, and Shibata, 2005;Qiu et al 2002Qiu et al , 2004Fletcher, Pollock, and Potts, 2004;Qiu and Yurchyshyn, 2005;Saba, Gaeng, and Tarbell, 2006) from which the energy-release rate can be deduced by assuming a constant Mach number (M) = 0.01 -0.1 (Isobe et al, 2002;Isobe, Takasaki, and Shibata, 2005;Lee, Gary, and Choe, 2006;Temmer et al, 2007;Miklenic et al, 2007).…”
Section: Introductionmentioning
confidence: 99%